2017
DOI: 10.1111/jdv.14719
|View full text |Cite
|
Sign up to set email alerts
|

Acne across Europe: an online survey on perceptions and management of acne

Abstract: Almost one-third of young people consider acne to be a major problem/burden. Fewer than half of acne diagnoses are made by a physician, and acne is often self-managed using OTC treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 15 publications
(32 reference statements)
5
27
1
1
Order By: Relevance
“…There are several reports which indicated the mass media especially internet as a popular source of information for patients (Brajac et al, 2004;Gokdemir, Fisek, Köslü, & Kutlubay, 2011;Szepietowski et al, 2018). In contrast to the results of the current study, most of the reports indicated that doctors were the most common source of information on acne to patients (Brajac et al, 2004;Gokdemir et al, 2011;Rigopoulos et al, 2007;Szepietowski et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…There are several reports which indicated the mass media especially internet as a popular source of information for patients (Brajac et al, 2004;Gokdemir, Fisek, Köslü, & Kutlubay, 2011;Szepietowski et al, 2018). In contrast to the results of the current study, most of the reports indicated that doctors were the most common source of information on acne to patients (Brajac et al, 2004;Gokdemir et al, 2011;Rigopoulos et al, 2007;Szepietowski et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
“…In this study, information on OIT among patients was obtained most frequently from friends, followed by family, internet, and physicians. Other recent studies have also found that family and friends are often consulted about acne (Al-Natour, 2017;Karciauskiene et al, 2015;Nguyen et al, 2016;Rigopoulos et al, 2007;Szepietowski et al, 2018). Saudi adolescent males and patients from United States reported the sources of information on acne, mostly mass media and internet in a different two studies (Al-Natour, 2017;Nguyen et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations